2022
DOI: 10.2169/internalmedicine.8223-21
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome of Inappropriate Antidiuretic Hormone Secretion as the Initial Presentation in a Patient with Stage I Small-cell Lung Cancer

Abstract: A 67-year-old man with a history of esophageal cancer resection was referred to our hospital because of nausea and appetite loss. Laboratory findings showed severe hyponatremia and were compatible with syndrome of inappropriate antidiuretic hormone (SIADH) secretion. Chest computed tomography (CT) revealed a nodule measuring 13 mm in the lower lobe of the right lung. Right thoracotomy was performed, and the histopathological diagnosis was small-cell lung cancer (T1bN0M0; Stage 1b). Although SIADH is frequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In addition, hyponatraemia is a common paraneoplastic syndrome caused by ectopic secretion of small cell lung cancer [16]. Tomonobu Koizumi et al [17] reported that about approximately 9%~15% of patients with small cell lung cancer had combined hyponatremia, which is usually closely related to the ectopic secretion of antidiuretic hormone by paraneoplastic tumours. Recalcitrant hyponatremia secondary to abnormal secretion of antidiuretic hormone (SIADH) is an independent risk factor for poor prognosis in patients with malignant tumours [17,18], and timely sodium supplementation therapy can signi cantly improve the survival prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, hyponatraemia is a common paraneoplastic syndrome caused by ectopic secretion of small cell lung cancer [16]. Tomonobu Koizumi et al [17] reported that about approximately 9%~15% of patients with small cell lung cancer had combined hyponatremia, which is usually closely related to the ectopic secretion of antidiuretic hormone by paraneoplastic tumours. Recalcitrant hyponatremia secondary to abnormal secretion of antidiuretic hormone (SIADH) is an independent risk factor for poor prognosis in patients with malignant tumours [17,18], and timely sodium supplementation therapy can signi cantly improve the survival prognosis of patients.…”
Section: Discussionmentioning
confidence: 99%